Analysis of T-Code Compression Methods to Increase Capacity of SSCE Method - Marzuki Leo; Charles Halim; Iola Iola; Jeremy Valtino; Insidini Fawwaz (Jurnal Mantik, 2020)
The process of hiding classified information can take advantage of the steganography method. However, media such as images, audio or video is not efficient, due to the large size of the media, making text media a great solution for hiding confidential information. In 2011, a new steganographic method was introduced that uses special code generation based on the use of unlimited articles or on conjunctions with nouns that are not specific or specific to English. A new code representation method Secret Steganography Code for Embedding (SSCE) was also used to increase security. However, there is a problem with the application of this text steganography method, namely that the secret message has not been compressed, where if the cover text is smaller than the secret message, the secret message cannot be inserted into the cover text. To solve this problem, a text compression method can be applied. One of the compression methods that can be applied is the T-Code text compression method. The T-Code method uses the concept of iterative code construction and self-synchronization to compress and decompress text. From the testing process, information was obtained that every change of letter or word in the position where the secret message bit is attached will cause the secret message that is extracted to become chaotic and the T-Code compression method can increase the capacity of the cover document by 10.61%.